HOW DID SARI COME INTO EXISTENCE - Bansal, Vishali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The origin of the sari, a traditional Indian garment, can be traced back to ancient civilizations, with its roots deeply embedded in cultural and historical significance. The sari's existence can be dated to as early as the Indus Valley Civilization (around 2800-1800 BCE), where archaeological findings depict draped fabric resembling the contemporary sari (Ranavaade, 2023). Over centuries, the sari evolved in style, reflecting the diverse cultural influences across regions in India. Historically, the sari was not only a symbol of modesty but also a canvas for artistic expression. Various weaving techniques, intricate patterns, and vibrant colors emerged, signifying regional traditions. The sari's draping style also evolved, adapting to social and cultural changes. As India experienced invasions and trade interactions, the sari incorporated diverse elements, resulting in a rich tapestry of styles. Throughout the centuries, the sari has transcended its functional purpose to become a symbol of cultural identity and femininity. Modern times have seen a fusion of traditional and contemporary designs, showcasing the adaptability and timelessness of this iconic garment. The journey of the sari from ancient civilizations to its present form reflects the dynamic nature of Indian culture and its ability to preserve tradition while embracing change.